The Alliance of Bioversity International and CIAT Annual Report 2020: Toward 2030: Food system transformation for healthier people and the planet - Bioversity International; International Center for Tropical Agriculture (2021)
Scientists reflect on food systems thinking approaches in the first year of the Alliance between Bioversity International and CIAT, amidst the context of the COVID-19 pandemic.